A novel approach to mapping FrameNet lexical units to WordNet synsets - Sara Tonelli; Emanuele Pianta (Proceedings of IWCS-8, 2009)
In this paper we present a novel approach to mapping FrameNet lexical units to WordNet synsets in order to automatically enrich the lexical unit set of a given frame. While the mapping approaches proposed in the past mainly rely on the semantic similarity between lexical units in a frame and lemmas in a synset, we exploit the definition of the lexical entries in FrameNet and the WordNet glosses to find the best candidate synset(s) for the mapping. Evaluation results are also reported and discussed.